KEBIJAKAN DAN PROGRAM DALAM PENGEMBANGAN TERNAK SAPI DI UPTD BALAI PEMBIBITAN TERNAK PETANGIS DINAS PERKEBUNAN DAN PETERNAKAN KABUPATEN PASER - Muslihuddin; Muh Jamal; Muhlis Hafel (Journal Publicuho, 2023)
This study aims to evaluate the existing condition of UPT. The Petangis Livestock Breeding Center (BPT) in Batu Engau District, Paser Regency, analyzed the State Mainstay Buffalo Cattle program (SIKOMANDAN), which has been running in Paser Belengkong District and analyzed plans for implementing the SIKOMANDAN program at UPT. BPT Crying. This research is descriptive in nature, with the technique of selecting respondents using purposive sampling and using EXTAND analysis to evaluate the existing condition of the UPT. BPT Crying. The results showed that the condition of infrastructure and human resources was generally not optimal to support performance optimization, especially for the provision of superior cattle breeds. Considering that the SIKOMANDAN Program in Paser Belengkong District can increase the population and quality of cattle breeds, the implementation of the program at UPT. BPT Petangis needs to complete the facilities and materials for Artificial Insemination (AI), fulfilment of health workers (Veterinary Medicine), training for reproductive workers for Pregnancy Examination (Pkb), carrying capacity of operational costs and activity results to be reported to Isikhnas.